Principles of continuous control - Rees, Amy; Kenworthy, Nancy; O'Leary, Steve; Brooks, Marv (Instrumentation video series, 1989)
The first program in a series designed to introduce technicians and engineers to the concepts used in industry to control the safety, quality and productivity of manufacturing processes.